Unresolved issues in the analysis of F2-isoprostanes, F4-neuroprostanes, isofurans, neurofurans, and F2-dihomo-isoprostanes in body fluids and tissue using gas chromatography/negative-ion chemical-ionization mass spectrometry. (July 2015) - Yen, H.-C.; Wei, H.-J; Lin, C.-L.
Abstract: F2 -isoprostanes (F2 -IsoPs) generated from arachidonic acid (AA) have been recognized as the most reliable marker of nonenzymatic lipid peroxidation in vivo . F2 -IsoPs are initially produced in esterified form on phospholipids, and then released into body fluids in free form. The same mechanism can lead to generation of F4 -neuroprostanes (F4 -NPs) and F2 -dihomo-IsoPs from docosahexaenoic acid (DHA) and adrenic acid, respectively. In addition, isofurans (IsoFs) and neurofurans (NFs) may be preferentially produced from AA and DHA, respectively, under high oxygen tension. The detection of F2 -IsoPs using gas chromatography/negative-ion chemical-ionization mass spectrometry (GC/NICI-MS) has been widely employed, which is important for human body fluids containing low quantity of free-form F2 -IsoPs. F4 -NPs have also been detected using GC/NICI-MS, but multiple peaks need to be quantified. In this paper, we summarize the basic workflow of the GC/NICI-MS method for analyzing F2 -IsoPs and F4 -NPs, and various formats of assays conducted by different groups. We then discuss the feasibility of simultaneous analysis of IsoFs, NFs, and F2 -dihomo-IsoPs with F2 -IsoPs or F4 -NPs. Representative GC chromatograms for analyzing these markers in human body fluids and rat brain tissue are demonstrated. Furthermore, we discuss several factors that may affect the performance of the analysis, such as those related to the sample processing steps, interference from specimens, types of GC liners used, and the addition of electron multiplier voltage in the method setting for the MS detector. Finally, we question the appropriateness of measuring total (free plus esterified) levels of these markers in body fluids.